On the informational and algorithmic complexities of some classes of Fredholm equations of the first kind - Perestyuk, M. О.; Mishura, Yu. S.; Ragulina, О.Yu. (Reports of the National Academy of Sciences of Ukraine, 2014)
The problems of minimization of computational efforts for the numerical solving of severely ill-posed problems are studied. A projection scheme of discretization, which is economical in a sense of used harmonics, is presented. Due to the scheme, the order estimates of the quantities characterizing the informational and algorithmic complexities are obtained.